PERENCANAAN KOMBINASI KEUANGAN: INTEGRASI KEPUTUSAN FINANSIAL SESUAI DENGAN PRINSIP SYARIAH - Jessika Gafur; Rika Dwi Ayu; Sudirman (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2026)
The Islamic financial system is a financial framework founded on the principles of the Qur'an and the Sunnah, aiming to promote justice, balance, and blessings in economic activities. Integrated Islamic financial planning has become an essential concept in modern financial management as it combines various financial decisions, including investment, financing, asset and liability management, risk control, and profit distribution in accordance with Islamic principles. This study aims to explain the concept of integrated financial planning from an Islamic perspective and its implementation in corporate financial management. The research employs a literature review method by examining various sources related to Islamic finance and Sharia financial management. The findings indicate that the Islamic financial system prohibits practices such as riba (usury), gharar (excessive uncertainty), maysir (gambling), and israf (extravagance), as these contradict the principles of justice and public welfare. In practice, the integration of Sharia-compliant financial decisions is carried out through Islamic contracts, including mudharabah, musyarakah, murabahah, ijarah, salam, and istisna'. Beyond profit maximization, Islamic financial planning also seeks to enhance social welfare through trustworthy, transparent, and productive fund management. Therefore, the implementation of integrated Islamic financial planning is expected to establish a fair, sustainable, and ethically responsible business system that brings benefits and blessings to all stakeholders. Keywords: Islamic Financial Planning, Integrated Financial Decision-Making, Islamic Finance, Sharia Investment, Sharia Financial Management.